(untitled) (Fiep Bulletin - online, 2015)
Ballet classes demands on the practitioners excellent physical conditioning with intense efforts, nevertheless there isn’t a specific determinant of effort intensity. For a better elucidation of this subject, the heart rate monitoring (HR) could indicate the state of physical conditioning of ballet dancers and the physiological intensities of the ballet class. Actually, the HR is considered the simpler, faster, easier and most directed method to indicate the powerful of an athlete during a maximum workout. The aim of this study was investigate the heart rate behavior during a classic ballet class. Participating this study 10 female classic ballet dancers, with minimum of 9 years of regular participating of classical ballet classes. After a rest period, the HR was measured in the entire sample. Then, we realized a maximum test in cycloergometer. The class is composed by 17 exercises, 9 exercises with ballet shoe realized in a bar support, 1 exercise with ballet shoe realized in the center of the class (no bar support); 7 exercises realized with ballet pointe shoe also in the center (without bar support), characterizing of higher difficulty and hard intensity. To data treatment we used the statistical procedures of descriptive statistics. The heart rate behavior was verified during a ballet class in female ballet dancers, and the results were demonstrated in relative values (%) of reserve HR and in beats per minute. The sample (20,83,08 years old, 51,94,04 kg, 164,36,34 cm, IMC of 19,481,31 kg/m2 and VO2max equivalent of 49,648,74 ml/kg/min) reached high intensity levels of exercise, like 79,58% of reserve HR and media maximum HR of 192,6 bpms. After the procedures of datas collected (class and maximum test) were possible to detect that ballet classes intensity are extremely high, because peaks above 60% of reserve heart rate are considerate intense, in accordance with datas of American College of Sports Medicine (2005). We hope that the elucidations of this study could take off some doubts of athlete’s physiological characterizations in a modality where training isn’t only physical but also artistical.